2014
DOI: 10.1002/ppap.201300141
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Pressure Non-Equilibrium Plasma Treatment to Improve the Electrospinnability of Poly(L -Lactic Acid) Polymeric Solution

Abstract: This work is focused on the use of non-thermal plasma to improve the electrospinnability of poly(L-lactic acid) (PLLA). The use of toxic high boiling point solvents is minimized to produce high quality solvent free nanofibrous scaffolds for biomedical applications. PLLA polymeric solutions dissolved in pure dichloromethane are exposed to the plasma plume of a jet developed by some of the authors and driven by high voltage pulses with rise rate of several kV ns À1 . The effects of peak voltage, pulse repetition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
48
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 24 publications
5
48
0
1
Order By: Relevance
“…Colombo et al. followed a similar strategy, using an atmospheric pressure plasma jet (APPJ) to treat polylactic acid dissolved in dichloromethane and observed 100% bead‐free fibers . In our research group, an extensive study on the effects of NTP exposure on a solution of PCL or PLLA in CHCl 3 and DMF was recently performed .…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Colombo et al. followed a similar strategy, using an atmospheric pressure plasma jet (APPJ) to treat polylactic acid dissolved in dichloromethane and observed 100% bead‐free fibers . In our research group, an extensive study on the effects of NTP exposure on a solution of PCL or PLLA in CHCl 3 and DMF was recently performed .…”
Section: Introductionmentioning
confidence: 89%
“…Without the addition of HFIP to chloroform, independent of the used electrospinning parameters, it has not been possible so far to obtain continuous bead‐free nanofibers. Driven by the need to find more effective, eco‐friendly, and biomedically benign strategies to improve the electrospinning process, several research groups have been investigating the potential of using atmospheric pressure plasma to improve polymer solution properties prior to electrospinning . The exposure of solids to non‐thermal plasma (NTP) is well described and has found a widespread use in many disciplines .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Shi et al have treated polyethylene oxide (PEO) and polyacrylonitrile (PAN) solutions and observed the creation of finer and smoother nanofibers after electrospinning. In another study by Colombo et al, plasma treatment was also found to promote the electrospinnability of poly‐ l ‐lactic acid (PLLA) solutions in dichloromethane resulting in the generation of nicely elongated smooth PLLA nanofibers. Inspired by the above‐mentioned works, our research group started to investigate the plasma treatment of poly‐ε‐caprolactone (PCL) solutions in a mixture of chloroform (CHL) and N , N ‐dimethylformamide (DMF) and also observed a significantly improved PCL nanofiber morphology as a result of PEPT .…”
Section: Introductionmentioning
confidence: 99%
“…Taking this into account, pre‐electrospinning plasma treatment (PEPT) of polymer solutions has already been investigated by several research groups, including ours, as an innovative and environmentally friendly method to change polymer solution properties in an effort to increase the electrospinnability of these solutions . For example, Shi et al have treated polyethylene oxide (PEO) and polyacrylonitrile (PAN) solutions and observed the creation of finer and smoother nanofibers after electrospinning.…”
Section: Introductionmentioning
confidence: 99%